Exploring motivation, goals, facilitators, and barriers to adopt health behaviors at retirement age: a focus group study - Paula Collazo-Castiñeira; Rocío Rodríguez-Rey; Gisela I. Delfino; Alfonso J. Cruz-Jentoft; Eva Topinková; Peter J. M. Weijs; Josje D. Schoufour; Macarena Sánchez-Izquierdo (BMC Public Health)
Abstract Background This study qualitatively investigates retirement-age adults' perspectives on engaging in health behaviors such as physical activity or a healthy diet, distinguishing facilitators, barriers, goals, and motivations (the two later in line with Self-Determination Theory). Methods Two clinical psychologists conducted four focus groups with Spanish adults around retirement age. We conducted inductive and deductive content analysis. Results The main facilitators and barriers identified were the presence and absence of social support/social network, mental health, willpower, time, and motivation. Participants reported different types of motivation (e.g., intrinsic motivation in the enjoyment of the activity of exercise or cooking) and goals (intrinsic and extrinsic); except for the goal of health management, which presented both types of motivation, participants regulated intrinsic goals autonomously, and extrinsic ones with controlled motivation. A process of internalizing the source of motivation was identified inductively by participants. Conclusions Facilitating social networks and addressing mental health issues could aid engagement in health behaviors among this population. Additionally, health management appeared as a significant goal, where autonomous motivation can develop even if the behavior initially arises from controlled motivation or external triggers, such as medical advice.